Complex Plagiarism: A Problem that Challenge Scientific Journal in the Present Day! - Viroj Wiwanitkit (Forensic Science Today - Peertechz Publications, 2015)
In science, the publication and presentation on the findings or ideas is the main step for generalization of new knowledge and support the development of the scientific community. An important problem that has been detected for a long time is an unethical practice, namely "plagiarism". Plagiarism is an action that one "steal" the "idea" or "word" or "picture" from the others. This problem is still prevalent in the present scientific community and it is an actual challenge for the society. Many plagiarisms can be seen and many plagiarists are detected. Of interest, some plagiarists have a high academic or administrative rank and get no problem from their bad practice. This problem is common in underdeveloped and developing countries (unbelievably, some plagiarists are deans, chancellors and scientists who get national awards) [1-3]. How to stop plagiarism is a topic that is widely discussed. The first step is to realize what the plagiarism is. Direct verbatim copy of word for writing or speaking are easily to detected as plagiarism. However, there are many forms of complex plagiarisms. The first example is the translational plagiarism. This is hard to detect but it is a real bad practice.